Pengaruh Self Help Group (SHG) Terhadap Tingkat Kecemasan Mahasiswa Profesi Ners Yang Terkonfirmasi Positif Covid-19 - Aprilia, Friska; Fahrizal, Yanuar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction – During the Corona Virus (Covid-19) pandemic whose cases are still up and down until now in March 2022, the prevalence of victims who were confirmed positive for Covid in Indonesia was around 5,948,610 and 153,411 victims who died. The Covid-19 incident which continues to increase every day has made health workers as frontline workers even more depressed due to increased workloads, increased anxiety about one's own health and fear of infecting others. Purpose – This study aims to determine the effect of Self Help Group (SHG) on anxiety levels in nursing professional students who are confirmed positive for COVID-19. Methodology/Approach – This study uses a quasi-experimental methods pre-test and post-test without control group, meaning that data collection is carried out before and after the intervention by giving a Self Help Group. The instrument used is HARS (Hamilton Anxiety Rating Scale) to measure the level of anxiety. Self Help Group is conducted four times a month, once a week with a total of 11 respondents. Findings intervention Self Help Group on a regular basis, in 11 nursing professional students there was a decrease in the level of anxiety. Anxiety experienced by students before being given the intervention was Very Severe Anxiety (46%), Severe Anxiety (18%), Mild Anxiety (18%), and No Anxiety (18%). After the intervention, there was a change in the level of anxiety with the results of Very Severe Anxiety (0%), Severe Anxiety (18%), Mild Anxiety (9%), and No Anxiety (73%). Originality/ Value/ Implication – Self Help Group has proven to be an effective intervention to reduce anxiety levels in nursing professional students who are confirmed positive for COVID-19.